IS HAVING DUAL INSURANCE DEMAND FOR BETTER HEALTHCARE FACILITY? - Sholikah, Badriyatus; Munaa, Nihayatul; Rahmawati, Nahardian Vica (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2025)
According to the Permenkes policy Number 3 of 2023, JKN participants can upgrade their treatment class by paying the difference either independently, through their employer, or through additional insurance. The decision to upgrade their treatment class can be influenced by several factors, such as social, personal, economic, and cultural factors. This study aims to analyze the factors that influence JKN patients' decisions to upgrade their treatment class at Dr. R. Sosodoro Djatikoesoemo Bojonegoro Regional Hospital. This study uses a quantitative cross-sectional approach. The population of this study were all JKN class 1 and 2 patients with a sample size of 92 respondents. The independent variables of this study were income, perception of services, availability of treatment rooms and ownership of additional insurance. The dependent variable was the decision to upgrade the class of care. This study used logistic regression analysis. This study was conducted at Dr. R. Sosodoro Djatikoesoemo Bojonegoro Regional Hospital. The results of bivariate analysis showed that the four independent variables had a significant effect on upgrading the in-patient care, i.e income p-value 0.000 (OR 4.312), perception of service p-value 0.000 (OR 1.362), availability of treatment rooms p-value 0.000 (OR 1.458), and ownership of additional insurance p-value 0.009 (OR 3.496). Whilst the multivariate analysis showed the most dominant factor was income p-value 0.000 (OR 4.571). In this study, it is expected that hospitals can consider service improvement strategies and understand patient segments which can later increase hospital revenue and overall service quality.